Die Institution des Doppelbesitzes an der ungarisch-jugoslawischen Grenze zwischen den beiden Weltkriegen - Hornyák, Árpád (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2012)
In many cases the borders driven by the Trianon Peace Treaty have cut villages from their properties, sometimes even the land properties were divided by the borders. The owners of these shared lands and the owners of those properties, which were divided by the borderline from their residency, were called double owners in the interwar period. Long-term regulation of the issue of double owners was in 1926 when the trade treaty was signed between Hungary and the Kingdom of Serbs, Croats and Slovenians. This treaty in its appendix regulated the border crossing, rights and duties of double owners until May 1932. However, after that date the issue caused serious difficulties since Yugoslavia wanted to abolish the institution of double ownership. The frictions reached a level that Hungary finally decided to ask the League of Nations' help. According to the decision of Geneve the two concerned states had to conduct bilateral negotiations in order to solve the matter. As the result of these negotiations an agreement was signed that strengthened the Hungarian position and kept the institution of double owners.
Keywords: Hungary; Madžarska; Jugoslavija; Yugoslavia; mejno območje; obmejna območja; dvolastništvo; Trianon; 1918-1940